2015
DOI: 10.1097/opx.0000000000000650
|View full text |Cite|
|
Sign up to set email alerts
|

Associations with Meibomian Gland Atrophy in Daily Contact Lens Wearers

Abstract: This study determined inconclusive associations with CLs and meibomian gland atrophy. This study also provided a comprehensive assessment of differences between CL and NCL wearers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 36 publications
2
57
3
Order By: Relevance
“…Pucker et al found no association between the area of meibomian gland atrophy and contact lens history, neither with subjective assessment nor with a semi-automatic approach, when using an univariate model. 30 Nichols and Sinnott did not report any structural changes in the glands of patients wearing rigid gas permeable or soft contact lenses. 31 In this study, all the analysed morphological characteristics of meibomian glands were worse initially for subjects with a previous history of contact lens wear.…”
Section: Discussionmentioning
confidence: 91%
“…Pucker et al found no association between the area of meibomian gland atrophy and contact lens history, neither with subjective assessment nor with a semi-automatic approach, when using an univariate model. 30 Nichols and Sinnott did not report any structural changes in the glands of patients wearing rigid gas permeable or soft contact lenses. 31 In this study, all the analysed morphological characteristics of meibomian glands were worse initially for subjects with a previous history of contact lens wear.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have shown that contact lens wear negatively affects the condition of meibomian glands, [30][31][32][33][34][35][36][37][38] although some have found no relation between lens wear and gland condition. [39][40][41] In wearers of rigid gas-permeable lenses, gland changes were detected at the temporal side in the upper eyelid, whereas wearers of soft contact lenses manifested linear shortening at the distal side in the lower eyelid ( Fig. 3).…”
Section: Contact Lens Wearmentioning
confidence: 99%
“…SL fogging may be made proportionally worse by fitting SL with a higher central corneal clearance, and it is a problem that can typically only be alleviated by the removing, cleaning, and reapplying of the lens [1,7,15,16]. While the community has begun to characterize SL fogging, there is still a lack of information related to other commonly reported minor CL complications like ocular redness and visual blur [17,18]. Therefore, the purpose of this study was to conduct a survey at an international specialty CL conference.…”
Section: Introductionmentioning
confidence: 99%